2013
DOI: 10.1104/pp.112.212340
|View full text |Cite
|
Sign up to set email alerts
|

MORE SPIKELETS1Is Required for Spikelet Fate in the Inflorescence of Brachypodium      

Abstract: Grasses produce florets on a structure called a spikelet, and variation in the number and arrangement of both branches and spikelets contributes to the great diversity of grass inflorescence architecture. In Brachypodium (Brachypodium distachyon), the inflorescence is an unbranched spike with a terminal spikelet and a limited number of lateral spikelets. Spikelets are indeterminate and give rise to a variable number of florets. Here, we provide a detailed description of the stages of inflorescence development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 48 publications
(61 reference statements)
5
50
0
1
Order By: Relevance
“…4). These results are consistent with the report that deletion in the Bradi1g18580 promoter causes inflorescence branching (Derbyshire and Byrne, 2013). Our findings with the closely related B. distachyon as a validation system confirm the role of FZP and more precisely AP2/ERF domain function in the determination of spike architecture in Triticeae.…”
Section: Wfzp-asupporting
confidence: 82%
See 3 more Smart Citations
“…4). These results are consistent with the report that deletion in the Bradi1g18580 promoter causes inflorescence branching (Derbyshire and Byrne, 2013). Our findings with the closely related B. distachyon as a validation system confirm the role of FZP and more precisely AP2/ERF domain function in the determination of spike architecture in Triticeae.…”
Section: Wfzp-asupporting
confidence: 82%
“…Derbyshire and Byrne (2013) isolated a B. distachyon mutant more spikelets1 (mos1) with similar defects in spikelet architecture; although no mutation in the coding region of FZP was found in this mutant, the authors proposed that the larger number of AxMs is due to a slightly but significantly lower expression of this AP2/ ERF transcription factor than in the wild type (20% less transcripts in the mos1 mutant). Derbyshire and Byrne (2013) suggested that this abnormal expression may be the consequence of a chromosome rearrangement affecting the promoter region of FZP. Here, we reported two new mutants sharing mutations in the highly conserved AP2/ERF domain of FZP and associated with an increased Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another type of variation, one or more spikelets are replaced by long lateral branches, which form their own spikelets and florets. Mutations of the WFZP-A/BH t -A1 gene, encoding an AP2/ERF transcription factor, lead to such noncanonical spike branching (Derbyshire and Byrne, 2013;Dobrovolskaya et al, 2015;Poursarebani et al, 2015), which is similar to the branching produced by mutating its orthologs in maize, rice, and Brachypodium distachyon (Chuck et al, 2002;Komatsu et al, 2003). Although these recent breakthroughs shed light on the molecular mechanisms underlying rare supernumerary spikelet variations, little is known about genetic factors affecting the architecture of archetypal wheat spike, its complexity, and grain yield.…”
mentioning
confidence: 99%